Strategi Pengembangan UMKM Pangan Melalui Kegiatan Kunjungan Lapang PS Pengembangan Industri Kecil Menengah, Sekolah Pascasarjana IPB - Hubeis, Musa (Institut Pertanian Bogor, 2021)
Micro-Small and Medium Enterprises (MSMEs) are one of business sector that has an important role for improving economy condition in Indonesia. One of the MSMEs that has the potential to competition and growth are food MSMEs. To create food MSMEs that able to compete and growth, they must be able to maintain the quality of various aspects by a development strategy. This research aims to create capacity and development strategy in food MSMEs based on company visit to three MSMEs in Bogor city. Solving the probem by descriptive approach and qualitative SWOT analysis. As a result, improvement for student at small medium industry (SMI) development, IPB poste graduate school can be carried and continuously to achieve the quality ad teaching and learning process, especially to combined theories and practices in the field to able to comprehend and analyze of food MSMEs s cases. From qualitative SWOT analysis could be implemented the development strategy of the food MSMEs in Bogor city as follow: (1) quality increase and variety of products to attract the consumers and maintain to; and (2) use of technology development and raw material existence to increase the production and markets